Mapping Zakat Potential at the City Level in Indonesia and Strategies for Optimizing Zakat Collection - Zaenal, Muhammad Hasbi; Noor, Zainulbahar; Hartono, Nono; Choirin, Muhammad; Salihovic, Elnur (Economica: Jurnal Ekonomi Islam, 2022)
Zakat, a core pillar of Islam, serves as an essential tool for wealth redistribution and socio-economic welfare. Despite Indonesia being home to the largest Muslim population globally, research on its zakat potential remains underdeveloped. This study aims to map the zakat potential across 510 cities and districts in Indonesia and propose strategies for optimizing zakat collection. Using the Indicators for Zakat Potential Mapping (IPPZ) framework developed by PUSKAS BAZNAS in 2019, secondary data from various official sources were aggregated to estimate zakat potential by province and zakat object. The results show that DKI Jakarta has the highest potential, totaling IDR 64.5 trillion, followed by East Java and West Java. Zakat on agricultural products, livestock, cash, corporate zakat, and professional income are the key contributors to this potential, with regional variations. The study's novelty lies in its detailed local-level zakat mapping, offering fresh insights into regional zakat potential. Additionally, it presents innovative strategies for enhancing zakat collection through decentralized efforts at the village, sub-district, and city levels, contributing to more effective zakat management and socio-economic development in Indonesia.